Multiple paternity in two natural populations (orchard and vineyard) of Drosophila. - Ochando, M D (1996)
Male mating success is an important fitness component in Drosophila. The seminal fluid conveyed with the sperm inhibits the proclivity of the female to remate and reduces her fitness. Nevertheless, females may remate before they have exhausted the sperm from the first male and consequently use sperm from both males. We have studied concurrent multiple paternity (CMP) in two Drosophila melanogaster populations, from an apple orchard and a vineyard just after harvest. CMP is high in both populations, somewhat greater than 50%; but it is not significantly higher in the vineyard, where the population density is much greater than in the orchard. Population density had been thought to be an important determinant of CMP incidence. We have used four gene loci coding for enzymes as independent markers for detecting CMP.